Aqueous aging of secondary organic aerosol coating onto black carbon: Insights from simultaneous L-ToF-AMS and SP-AMS measurements at an urban site in southern China. (1st January 2022) - Cao, Li-Ming; Wei, Jing; He, Ling-Yan; Zeng, Hui; Li, Meng-Lin; Zhu, Qiao; Yu, Guang-He; Huang, Xiao-Feng
Abstract: Secondary organic aerosol (SOA) in the atmosphere can be formed from the gas phase precursors and evolve in the particle phase. Compared to numerous studies on gas phase oxidation of volatile organic compounds (VOCs), the evolution of OA and corresponding mechanisms in the particle phase are still unclear. In this study, a thermodenuder (TD) was coupled with both a long time-of-flight aerosol mass spectrometer (L-ToF-AMS) and a soot particle aerosol mass spectrometer (SP-AMS) at an urban site in southern China during wintertime of 2018, to explore whether there is significant difference for OA evolution on black carbon (BC) aerosols. The OA measured by L-ToF-AMS and SP-AMS were resolved into different primary and secondary factors, with the OA factors on BC particles showed different volatilities to that on the bulk aerosol. The more-oxidized oxygenated OA (MO-OOA, an agent of aged SOA) exhibited a unique preference on BC particles compared to other OA components. The abundant transition metals detected on BC particles was possibly the catalyser for the transformation from less oxidized OOA (LO-OOA, an agent of fresh SOA) to MO-OOA in aerosol aqueous-phase on BC particles and thus facilitates SOA formation. More studies are needed to further explore the potential role of BC and transition metals as catalysers for OA aging and the co-benefit of BC and transition metals pollution control on SOA reduction in the atmosphere. Graphical abstract: Image 1 Highlights: MO-OOA exhibited a unique preference on BC particles compared to other OA components. The abundant transition metals detected on BC particles was possibly the catalyser for the transformation from fresh LO-OOA to more aged MO-OOA in aerosol aqueous-phase on BC particles. The reduction of primarily emitted BC and transition metals could further benefit the reduction of SOA.